Isolated & combined wearable technology underestimate the total energy expenditure of professional young rugby league players; a doubly labelled water validation study - Costello, N.; Deighton, K.; Cummins, C.; Whitehead, S.; Preston, T.; Jones, B. (The Journal of Strength and Conditioning Research, 2022)
Accurately determining total energy expenditure (TEE) enables the precise manipulation of energy balance within professional collision-based sports. Therefore, this study investigated the ability of isolated or combined wearable technology to determine the TEE of professional young rugby league players across a typical preseason and in-season period. Total energy expenditure was measured via doubly labelled water, the criterion method, across a fourteen-day preseason (n = 6) and 7-day in-season (n = 7) period. Practical measures of TEE included SenseWear Pro3 Armbands in isolation and combined with metabolic power derived from microtechnology units. SenseWear Pro3 Armbands significantly under-reported preseason (5.00 [2.52] MJ/d; p = 0.002) and in-season (2.86 [1.15] MJ/d; p < 0.001) TEE, demonstrating a large and extremely large standardized mean bias, and a very large and large typical error, respectively. Combining metabolic power with SenseWear Pro3 Armbands almost certainly improved preseason (0.95 [0.15] MJ/d; Effect size = 0.32 ± 0.04; p < 0.001) and in-season (1.01 [0.15] MJ/d; ES = 0.88 ± 1.05; p < 0.001) assessment. However, SenseWear Pro3 Armbands combined with metabolic power continued to significantly under-report preseason (4.04 [2.38] MJ/d; p = 0.004) and in-season (2.18 [0.96] MJ/d; p = 0.002) expenditure, demonstrating a large and very large standardized mean bias, and a very large and large typical error, respectively. These findings demonstrate the limitations of utilizing isolated or combined wearable technology to accurately determine the TEE of professional collision-based sport athletes across different stages of the season.